Cross‐coupling reactions in water using ionic liquid‐based palladium(II)–phosphinite complexes as outstanding catalysts. (29th September 2014) - Meriç, Nermin; Aydemir, Murat; Işik, Uğur; Ocak, Yusuf Selim; Rafikova, Khadichakhan; Paşa, Salih; Kayan, Cezmi; Durap, Feyyaz; Zazybin, Alexey; Temel, Hamdi
<x xml:space="preserve">Abstract</x> Two new phosphinite ligands based on ionic liquids [(Ph2PO)C7H14N2Cl]Cl (1) and [(Cy2PO)C7H14N2Cl]Cl (2) were synthesized by reaction of 1‐(3‐chloro‐2‐hydoxypropyl)‐3‐methylimidazolium chloride, [C7H15N2OCl]Cl, with one equivalent of chlorodiphenylphosphine or chlorodicyclohexylphosphine, respectively, in anhydrous CH2Cl2 and under argon atmosphere. The reactions of 1 and 2 with MCl2(cod) (M = Pd, Pt; cod = 1, 5‐cyclooctadiene) yield complexes cis‐[M([(Ph2PO)C7H14N2Cl]Cl)2Cl2] and cis‐[M(Cy2PO)C7H14N2Cl]Cl)2Cl2], respectively. All complexes were isolated as analytically pure substances and characterized using multi‐nuclear NMR and infrared spectroscopies and elemental analysis. The catalytic activity of palladium complexes based on ionic liquid phosphinite ligands 1 and 2 was investigated in Suzuki cross‐coupling. They show outstanding catalytic activity in coupling of a series of aryl bromides or aryl iodides with phenylboronic acid under the optimized reaction conditions in water. The complexes provide turnover frequencies of 57 600 and 232 800 h−1 in Suzuki coupling reactions of phenylboronic acid with p‐bromoacetophenone or p‐iodoacetophenone, respectively, which are the highest values ever reported among similar complexes for Suzuki coupling reactions in water as sole solvent in homogeneous catalysis. Furthermore, the palladium complexes were also found to be highly active catalysts in the Heck reaction affording trans‐stilbenes. Copyright © 2014 John Wiley & Sons, Ltd.